Pengaruh Return On Equity (ROE) dan Gross Profit Margin (GPM) Terhadap Pertumbuhan Laba Pada Bank Umum Syariah (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2023)
This research aims to determine the influence of two X variables, namely Return On Equity (X1) and Gross Profit Margin (X2) on Profit Growth (Y) on the Indonesian Stock Exchange with 30 samples from 6 Sharia Commercial Banks. This research uses a type of research using panel data. This research is a causal type of research with a quantitative approach. The data analysis method used is multiple linear regression with SPSS 26 software. The t-test results of the Return On Equity (X1) variable show t-test  > ttable, namely 4.906 > 2.050 with a sig value of 0.000 < 0.05, it can be concluded that Ha1 is accepted and Ha0 is rejected. From the results of the t-test for the Gross Profit Margin (X2) variable, it shows tcount > ttable, namely 0.254 < 2.050 with a sig value of 0.801 > 0.05, it can be concluded that Ha2 is rejected and Ha0 is accepted. The test results obtained at Sharia Commercial Banks show that there is a significant influence of the independent variables simultaneously on the dependent variable, so Ha3 is accepted, namely that there is a positive and significant influence of the Return On Equity and Gross Profit Margin variables on Profit Growth.
Keywords: Return On Equity; Gross Profit Margin; Pertumbuhan Laba